Hydroxyethylamine Based Phthalimides as New Class of Plasmepsin Hits: Design, Synthesis and Antimalarial Evaluation - Singh, Anil K.; Rathore, Sumit; Tang, Yan; Goldfarb, Nathan E.; Dunn, Ben M.; Rajendran, Vinoth; Ghosh, Prahlad C.; Singh, Neelu; Latha, N.; Singh, Brajendra K.; Rawat, Manmeet; Rathi, Brijesh (PLOS ONE, 2015)
A novel class of phthalimides functionalized with privileged scaffolds was designed, synthesized and evaluated as potential inhibitors of plasmepsin 2 (Ki: 0.99 ± 0.1 μM for 6u) and plasmepsin 4 (Ki: 3.3 ± 0.3 μM for 6t), enzymes found in the digestive vacuole of the plasmodium parasite and considered as crucial drug targets. Three compounds were identified as potential candidates for further development. The listed compounds were also assayed for their antimalarial efficacy against chloroquine (CQ) sensitive strain (3D7) of Plasmodium falciparum. Assay of twenty seven hydroxyethylamine derivatives revealed four (5e, 6j, 6o and 6s) as strongly active, which were further evaluated against CQ resistant strain (7GB) of P. falciparum. Compound 5e possessing the piperidinopiperidine moiety exhibited promising antimalarial activity with an IC50 of 1.16 ± 0.04 μM. Further, compounds 5e, 6j, 6o and 6s exhibited low cytotoxic effect on MCF-7 cell line. Compound 6s possessing C2 symmetry was identified as the least cytotoxic with significant antimalarial activity (IC50: 1.30 ± 0.03 μM). The combined presence of hydroxyethylamine and cyclic amines (piperazines and piperidines) was observed as crucial for the activity. The current studies suggest that hydroxyethylamine based molecules act as potent antimalarial agent and may be helpful in drug development.